2020
DOI: 10.3390/vaccines8010062
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Modified Mouse Mesenchymal Stem Cells Expressing Non-Structural Proteins of Hepatitis C Virus Induce Effective Immune Response

Abstract: Hepatitis C virus (HCV) is one of the major causes of chronic liver disease and leads to cirrhosis and hepatocarcinoma. Despite extensive research, there is still no vaccine against HCV. In order to induce an immune response in DBA/2J mice against HCV, we obtained modified mouse mesenchymal stem cells (mMSCs) simultaneously expressing five nonstructural HCV proteins (NS3-NS5B). The innate immune response to mMSCs was higher than to DNA immunization, with plasmid encoding the same proteins, and to naïve unmodif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 77 publications
2
24
0
Order By: Relevance
“…In a pre-clinical model, Liu et al [ 117 ] reported that transplantation of MSCs expressing short hairpin RNA against hepatitis viral proteins (HBV S and HBV X) significantly reduced HBV antigens in the liver and serum. Masalova et al [ 179 ] tested the efficacy of utilizing MSCs as an immunization agent against HCV and found that murine BM-MSCs expressing five non-structural HCV proteins induced significantly higher proliferation of lymphocytes, IFN-γ secretion, and IgG2a levels compared to naked DNA immunizations suggesting the feasibility of utilizing modified MSCs as vaccine agents. Hypoxic pre-conditioning also improves the migration, survival, and anti-inflammatory properties of MSCs[ 174 , 180 , 181 ].…”
Section: Genetic Modifications and Priming Of Mscsmentioning
confidence: 99%
“…In a pre-clinical model, Liu et al [ 117 ] reported that transplantation of MSCs expressing short hairpin RNA against hepatitis viral proteins (HBV S and HBV X) significantly reduced HBV antigens in the liver and serum. Masalova et al [ 179 ] tested the efficacy of utilizing MSCs as an immunization agent against HCV and found that murine BM-MSCs expressing five non-structural HCV proteins induced significantly higher proliferation of lymphocytes, IFN-γ secretion, and IgG2a levels compared to naked DNA immunizations suggesting the feasibility of utilizing modified MSCs as vaccine agents. Hypoxic pre-conditioning also improves the migration, survival, and anti-inflammatory properties of MSCs[ 174 , 180 , 181 ].…”
Section: Genetic Modifications and Priming Of Mscsmentioning
confidence: 99%
“…Some studies have shown that MSC-secreted factors can have anti-bacterial and anti-viral activities [193,194]. Indeed, several cytokines including IL-6, IL-10 and TNF-α have been shown to fluctuate during bacterial infection [195][196][197][198][199]. Meisel and colleagues demonstrated that MSCs stimulated by inflammatory cytokines display antimicrobial activities against several bacteria, protozoal parasites and viruses [193].…”
Section: Paracrine Properties Of Mscsmentioning
confidence: 99%
“…Analysis of lymphocyte proliferation during treatment of the compounds was carried out as described previously [65]. Splenocytes were isolated from the mice, washed with the RPMI-1640 medium (Paneco, Moscow, Russia), and seeded onto 96-well plates at a density of 5 × 10 6 per well in the RPMI-1640 medium supplemented with 20% fetal calf serum (Invitrogen, Waltham, MA, USA), 2 mM glutamine, 4.5 mg/mL glucose, 50 µg/mL gentamycin, and 0.2 U/mL insulin.…”
Section: Lymphocyte Proliferation Assaymentioning
confidence: 99%